2018
DOI: 10.1016/j.smallrumres.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean silage on feeding behavior, performance, and meat quality of lambs

Abstract: The objective of this study was to evaluate the performance, feeding behavior, carcass traits, and meat quality of feedlot lambs using 2 types of silage, sorghum or soybean. Twenty-eight male non-castrated market lambs weighting 20 ± 2 kg were used. Diets were formulated to be isonitrogenous and isocaloric. The animals were slaughtered after 50 days of experiment, with 32.13 ± 5.09 kg of body weight. Lambs fed with soybean silage showed increased time for feed intake (P = 0.01). There was no difference for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
1
5
1
1
Order By: Relevance
“…The carcass traits were not significantly different among the four treatments (Table 5). This is in agreement with the present study, which did not observe any difference in the carcass morphometric measurement among the different diets [35] and oil seed meal diet [23].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The carcass traits were not significantly different among the four treatments (Table 5). This is in agreement with the present study, which did not observe any difference in the carcass morphometric measurement among the different diets [35] and oil seed meal diet [23].…”
Section: Discussionsupporting
confidence: 94%
“…Some studies about diet nutrition with meat quality were conducted in sheep [36][37][38][39][40][41][42][43][44][45]. Protes et al (2018) reported the decreased shear force of samples from lambs fed with soybean silage compared to sorghum. The finding indicated that the PH of meat could be a good indicator of pork quality and related to factors influencing the pork eating quality [46].…”
Section: Discussionmentioning
confidence: 99%
“…Reséndiz et al (2013) evaluated a whole food diet for sheep with 30% alfalfa, and found a greater DMI (36%), this difference is attributed to the fact that the lambs used had higher LW (22.1 vs 15.51 kg) when compared to the lambs used in the present study. On the other hand, Protes et al (2018) did not find differences in DMI in lambs fed with silage made from soybean and sorghum fodder. However, Lima et al (2013) reported higher DM intake in lambs fed with silage made from soybean and sugarcane tips.…”
Section: Resultscontrasting
confidence: 63%
“…Therefore, we hypothesized that microbial inoculant or chitosan addition in WPSS reduces silage losses, increases lactic acid and DM degradation of silages. Protes et al (2018) evaluated wholeplant soybean silage in replacement to sorghum silage. Soybean silage provides the same animal performance, carcass traits, and economic benefit compared with the sorghum silage diet.…”
Section: Introductionmentioning
confidence: 99%